2013
DOI: 10.1080/01419870.2013.821147
|View full text |Cite
|
Sign up to set email alerts
|

Off white: colour-blind ideology at the margins of whiteness

Abstract: This study examines the relationship between racial contestation and colourblind ideology adherence. Using the first nationally representative study to ask respondents directly about personal racial identity and external racial ascription, I compare the racial conceptualizations of contested and noncontested whites. Contested whites are individuals who identify racially as white, but who are perceived by others as non-white. Contested whites find themselves at the margins of whiteness, betwixt and between cate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 62 publications
(77 reference statements)
0
33
0
Order By: Relevance
“…Within the framework of race being socially constructed, social science research has provided two general approaches to measure race; self-identification and social-assignment or ascribed race. Much of the research interested in exploring disparities across racial/ethnic groups has typically relied on asking respondents to self-identify their race/ethnicity in surveys (Lewis 2003; Saperstein 2006; Roth 2010; Stepanikova 2010; Campbell and Troyer 2011; Cheng and Powell 2011; Veenstra 2011; Saperstein 2012; Song and Aspinall 2012; N. Vargas 2014).…”
Section: Socially Assigned Race Stereotypes and Discrimination Of Mmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the framework of race being socially constructed, social science research has provided two general approaches to measure race; self-identification and social-assignment or ascribed race. Much of the research interested in exploring disparities across racial/ethnic groups has typically relied on asking respondents to self-identify their race/ethnicity in surveys (Lewis 2003; Saperstein 2006; Roth 2010; Stepanikova 2010; Campbell and Troyer 2011; Cheng and Powell 2011; Veenstra 2011; Saperstein 2012; Song and Aspinall 2012; N. Vargas 2014).…”
Section: Socially Assigned Race Stereotypes and Discrimination Of Mmentioning
confidence: 99%
“…In work that examines racial misclassification, Campbell and Troyer (2011) find that misclassified American Indians have higher rates of psychological distress (Campbell and Troyer 2011). Similarly, in what scholars have labeled the “whitening of Latina/os,” recent work by Vargas (2014) has shown that respondents who report higher socioeconomic status and lighter skin are more likely to be viewed as white compared to respondents who have lower socioeconomic status and darker skin (Vargas 2014). …”
Section: Socially Assigned Race Stereotypes and Discrimination Of Mmentioning
confidence: 99%
“…Increasingly, scholarship on racial measurement has taken up this task, and a set of literature on contested racial identities is emerging. Survey based studies are considering the contexts within which racial identity contestation takes place (Feliciano ; Vargas ), how common it is (Porter et al ; Saperstein ; Vargas and Stainback ), its implications for individuals' health (Campbell and Troyer , ; Stepanikova ; Veenstra ), social status (Penner and Saperstein , 2010; Stepanikova ), experiences of arrest and discrimination (Penner and Saperstein ; Vargas et al forthcoming) and perceptions of race and identity (Saperstein and Penner ; Trujillo et al ; Vargas , Vargas and Stainback ). This literature is primarily focused on monoracial identifying adults and is influenced theoretically by a larger set of scholarship on the complex navigation of identity among multiracial identifiers (Brunsma ; Davenport ; Doyle and Kao ; Franco and Franco forthcoming; Harris and Sim ; Khanna ; Khanna and Johnson ; Rockquemore ; Rockquemore and Brunsma ; Rockquemore et al ; Sims forthcoming).…”
mentioning
confidence: 99%
“…Prior research has examined conflicts between expressed (self) and observed (interviewer/other) racial identifications (e.g., see Campbell and Troyer 2007;Roth 2010;Saperstein 2006;Vargas 2013;Veenstra 2011;Wilkinson 2010). We focus, however, on discrepancies within expressed and observed identifications.…”
Section: Inconsistent Expressed and Observed Racial Identificationsmentioning
confidence: 99%
“…Given variable dynamics of social interactions, observers' decisions about respondents' racial identifications could be inconsistent across observers or even over time. Furthermore, research has shown that individuals have a sense of how observers classify them (Campbell and Troyer 2011;Stepanikova 2010;Vargas 2013). Perceptions that vary across observers likewise influence the identity standard (Burke 1991(Burke , 2006.…”
Section: Racial Inconsistency Skin Color and American Indians' Mentmentioning
confidence: 99%